(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this research work, the in vitro propagation of Alternanthera ficoidea, an ornamental plant belonging to the Amaranthaceae familynative to South America, was carried out. This plant is considered important due to the presence of important pharmaceutical productssuch as tannins, saponins, phytols, carotenoids, xanthophylls and polyphenols, which is why it can be included as a medicinal herb aswell as being used colloquially as a tranquilizer and as a treatment for gastritis. This method guarantees to obtain a large number ofhomogeneous explants from the mother plant tissue, taking advantage of the division and regeneration capacity that plant cells possesswhen they are in adequate conditions for their growth. To achieve this in vitro establishment, three disinfection methods were evaluated,obtaining a greater number of viable explants with the use of 0.1% mercuric chloride for 5 min and greater shoot growth with thecombination of phytohormones (1.5 + 1.5 mg.L-1 of AG3 and BAP respectively) reaching an average shoot length of 3.7 cm. Theseseedlings were acclimatized to nursery conditions.